Intranasally Co-administered Berberine and Curcumin Loaded in Transfersomal Vesicles Improved Inhibition of Amyloid Formation and BACE-1 - Mishra G.; Awasthi R.; Singh A.K.; Singh S.; Mishra S.K.; Singh S.K.; Nandi M.K. (My University, 2025)
Selective permeability of the blood-brain barrier restricts the treatment efficacy of neurologic diseases. Berberine (BBR) and curcumin (CUR)-loaded transferosomes (TRANS) were prepared for the effective management of Alzheimer's disease (AD). The study involved the syntheses of BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS by the film hydration method. Vesicles were characterized to ensure the formation of drug-loaded vesicles and their in vivo performance. The particle sizes of BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS were 139.2 ± 7, 143.4 ± 8, and 165.3 ± 6.5 nm, respectively. The presence of diffused rings in the SED image indicates the crystalline nature of the payload. Low surface roughness in an AFM image could be associated with the presence of a surface lipid. BBR-CUR-TRANS showed 41.03 ± 1.22 and 47.79 ± 3.67% release of BBR and 19.22 ± 1.47 and 24.67 ± 1.94% release of CUR, respectively, in phosphate buffer saline (pH 7.4) and acetate buffer (pH 4.0). Formulations showed sustained release of both loaded drugs. BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS exhibited a lower percentage of hemolysis than pure BBR and CUR, indicating the safety of the payload from delivery vesicles. Lower percentages of binding were recorded from BBR-CUR-TRANS than BBR-TRANS and CUR-TRANS. Acetylcholinesterase inhibition activity of the prepared transferosomes was greater than that of pure drugs, which are thought to have good cellular penetration. The spatial memory was improved in treated mice models. The level of malondialdehyde decreased in AD animals treated with BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS, respectively, as compared to the scopolamine-induced AD animals. BBR-CUR-TRANS-treated animals showed the highest decrease in the NO level. The catalase level was significantly restored in scopolamine-intoxicated animals treated with BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS. The immunohistochemistry result suggested that the BBR-TRANS, CUR-TRANS, and BBR-CUR-TRANS have significantly decreased the regulation of expression of BACE-1 through antioxidant activity. In conclusion, the study highlights the utility of formulated transferosomes as promising carriers for the co-delivery of drugs to the brain. © 2022 American Chemical Society. All rights reserved.